2001
DOI: 10.1093/ageing/30.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between age and plasma esterases

Abstract: age per se is not associated with reductions in the activities of esterase enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 0 publications
1
15
0
5
Order By: Relevance
“…Based on this observation, it was suggested that AChE activity could be an excellent enzymatic marker for RBC aging in humans 5 although the plasma activity of AChE has been shown to be unaffected by age in humans 30 . Our results show significant age-dependent decrease in the activity of membrane bound AChE in a mixed a population of red blood cells and is the first report of an agedependent decline in AChE in humans.…”
Section: Resultsmentioning
confidence: 99%
“…Based on this observation, it was suggested that AChE activity could be an excellent enzymatic marker for RBC aging in humans 5 although the plasma activity of AChE has been shown to be unaffected by age in humans 30 . Our results show significant age-dependent decrease in the activity of membrane bound AChE in a mixed a population of red blood cells and is the first report of an agedependent decline in AChE in humans.…”
Section: Resultsmentioning
confidence: 99%
“…esterases), the effect of age itself has been debated. In a study of 113 healthy subjects aged between 18 and 85 years, no correlation was found between esterase enzyme activity and increasing age (Abou-Hatab et al, 2001). Similarly, for Phase II reactions, physical status has a significant effect on the hepatic drug clearance of medications.…”
Section: Age-associated Physiological Alterations (Physiological Age)mentioning
confidence: 96%
“…En 2001, Abou-Hatab y colaboradores no hallaron correlación entre los valores de actividad colinesterásica plasmática y edad, al estudiar 70 personas sanas de 18 a 85 años (22). Lo anterior (1,22) concuerda con nuestros hallazgos, pero debe anotarse que nuestros valores en adultos son francamente superiores a los hallados por Henao y colaboradores (7) en adolescentes de 14-17 años.…”
Section: Monotest® Plasmaunclassified